قاعدة سد الذرائع وبعض تطبيقاتها الطبية - بالنور, نعيمة (University of Eloued جامعة الوادي, 2017)
يعالج هذا البحث قاعدة ذات أهمية بالغة في أصول الفقه، ألا وهي "قاعدة سد الذرائع وتطبيقاتها الطبية" وحاول البحث الإجابة على عدة إشكاليات أهمها: معنى سد الذرائع، ومدى مشروعية العمل بها. كما تناول البحث دراسة تطبيقية لبعض المستجدات الطبية المتعلقة بهذه القاعدة وهي: حكم مداواة الرجل للمرأة، نقل الأعضاء ورتق غشاء البكارة، وكذا حكم إجهاض الأجنة المشوهة. وفي الأخير توج هذا البحث بخاتمة تضمنت أهم النتائج المتوصل إليها. This research deals with a rule of great importance in the fundamentals of jurisprudence, namely, "the rule of blocking excuses and their medical applications." The research attempted to answer several problems, the most important of which are: the meaning of filling the excuses and the legitimacy of the work. The study also dealt with an applied study of some medical developments related to this rule: the rule of man's treatment of women, transplants and hymen, as well as the rule of abortion of deformed embryos. Finally, this research culminated in a conclusion that included the most important findings.
مذكرة ماستر تخصص اصول فقه
Keywords: سد الذرائع، المداواة، نقل الأعضاء، الرتق، الإجهاض، الجنين المشوه; Blocking excuses, healing, organ transplants, darn, abortion, deformed fetus